Dendrodorididae (Heterobranchia, Nudibranchia) from Persian Gulf with a description of a new species of Doriopsilla and remarks on the family - Maniei, Fatemeh; Wägele, Heike (European Journal of Taxonomy, 2024)
The family Dendrodorididae has a global distribution, with prevalence in tropical and subtropical intertidal zones. Three species of Dendrodorididae were collected from the intertidal zone of the northern coast of the Persian Gulf in Iran. Based on anatomical, histological, and molecular investigations they can be assigned to Dendrodoris fumata, Dendrodoris nigra, and a new species of Doriopsilla, D. aroni sp. nov. Molecular analyses of CO1 and 16S, including all genera of Dendrodorididae, members of the sister taxon Phyllidiidae, and other dorid outgroups resulted in a polyphyletic genus Dendrodoris, which is in contrast to the nuclear gene studies. Our molecular results confirm the differentiation between Dendrodoris rubra and D. fumata. Dendrodoris nigra, D. fumata, and D. krusensternii each consist of several clades, indicating cryptic species complexes requiring further investigation. We describe the presence of bacteria for the first time in the vestibular gland of D. fumata. Validation of the specimens of Doriopsilla from the Persian Gulf as a new species is supported by haplotype networking, genetic distance, and ABGD analyses of mitochondrial genes. Our CO1 analysis confirms a previous hypothesis that Cariopsilla is a junior synonym of Doriopsilla.